1988
DOI: 10.1093/nar/16.17.8207
|View full text |Cite
|
Sign up to set email alerts
|

Codon usage patterns inEscherichia coli, Bacillus subtilis, Saccharomyces cerevisiae, Schizosaccharomyces pombe, Drosophila melanogasterandHomo sapiens; a review of the considerable within-species diversity

Abstract: The genetic code is degenerate, but alternative synonymous codons are generally not used with equal frequency. Since the pioneering work of Grantham's group it has been apparent that genes from one species often share similarities in codon frequency; under the "genome hypothesis" there is a species-specific pattern to codon usage. However, it has become clear that in most species there are also considerable differences among genes. Multivariate analyses have revealed that in each species so far examined there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
305
0
4

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 559 publications
(334 citation statements)
references
References 13 publications
(12 reference statements)
16
305
0
4
Order By: Relevance
“…The predicted amino acid sequence contains peptide T2 but not Ti or Cl. Codon usage for both genes follows the trend observed in S. cerevisiae for proteins expressed at low levels (Sharp et al, 1988).…”
Section: Resultssupporting
confidence: 64%
“…The predicted amino acid sequence contains peptide T2 but not Ti or Cl. Codon usage for both genes follows the trend observed in S. cerevisiae for proteins expressed at low levels (Sharp et al, 1988).…”
Section: Resultssupporting
confidence: 64%
“…In contrast, lowly expressed genes are found exclusively at the left side of the plot (not shown). The data suggest that translation selection contributes to codon bias in lactobacilli, as it does in other micro-organisms (23).…”
Section: Codon Usage In Lactobacillusmentioning
confidence: 73%
“…Genes with high CAI values in fast-growing organisms are commonly interpreted as those which are involved in maintaining this growth rate or in enzymatic activities with a rapid response (Gouy and Gautier 1982;Sharp and Li 1987;Sharp et al 1988;Me´digue et al 1991;Shields and Sharp 1987;Carbone et al 2004). Genes with such properties are coding for ribosomal proteins, heat shock proteins, antioxidant proteins, proteins involved in the respiratory chain, structural genes (for eukaryotes), and enzymes involved in the metabolic pathways of amino acids biosynthesis.…”
Section: Metabolic Activities Derived From Cai Valuesmentioning
confidence: 99%
“…High expression rates of certain genes during exponential growth, or of enzymes involved in fundamental metabolic activities like glycolysis, have been very often reported in the literature for fast growers and studied, since the 1980s, through the notion of the Codon Adaptation Index (CAI) (Sharp and Li 1987). For fast-growing organisms like Escherichia coli and Saccharomyces cerevisiae, but also Caenorhabditis elegans and Dro-sophila melanogaster, genes have been ranked by CAI values and correlated with gene expression levels and functional activity (Sharp and Li 1987;Sharp et al 1986Sharp et al , 1988Shields and Sharp 1987;Stenico et al 1994). Carbone et al (2003) showed that the CAI can be defined purely by sequence analysis, that it can be calculated for genomes of organisms whose biological activities are not known, and that the resulting ranking of genes correlates well with the dominant codon bias of the organism.…”
Section: Introductionmentioning
confidence: 99%